A Soluble Immune Effector Binds Both Fungi and Bacteria via Separate Functional Domains - Liberti, Assunta; Cannon, John P.; Litman, Gary W.; Dishaw, Larry J. (Frontiers in Immunology, 2019)
The gut microbiome of animals consists of diverse microorganisms that include both prokaryotes and eukaryotes. Complex interactions occur among these inhabitants, as well as with the immune system of the host, and profoundly influence the overall health of both the host and its microbial symbionts. Despite the enormous importance to the host of regulation of its gut microbiome, it remains unclear whether or not hosts generate molecules with the capacity to directly mediate microbial interactions. The urochordate, Ciona robusta, is a model organism that has been adapted to experimental studies of host/microbiome interactions. Ciona variable-region containing chitin-binding proteins (VCBPs), which are composed of immunoglobulin (Ig) variable regions and a chitin-binding domain (CBD), are innate immune effectors expressed in high abundance in the Ciona gut. It was previously shown that VCBP-C binds bacteria and influences both phagocytosis by granular amoebocytes and biofilm formation via its Ig domains. We show here that the CBD of VCBP-C independently recognizes chitin molecules present in the cell walls, sporangia (spore-forming bodies), and spores of a diverse set of filamentous fungi isolated from the Ciona gut. To our knowledge, this is the first description of a secreted Ig-containing immune molecule with the capacity to directly promote transkingdom interactions through simultaneous binding by opposing structural domains. Features such as those described here, among secreted immune effectors, likely have broad implications in modulating the establishment, succession and homeostasis of gut microbiomes.